INTEGRATING ARTIFICIAL INTELLIGENCE (AI) TECHNOLOGY TO IMPROVE TOEFL SCORES FOR STUDENTS OF SMAN 19 BANDUNG - Nugraha, Deden Novan Setiawan; Gunawan, Hero; Dianita, Dianita; Sari, Puspita; Rusyan, Susiyanti; Simatupang, Ervina CM (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service program aimed to provide training on the integration of Artificial Intelligence (AI) technology to improve TOEFL scores among twelfth-grade students at SMAN 19 Bandung. The method employed in this program involved training and mentoring, which consisted of two main stages: the implementation stage (preparation and training) and the evaluation stage. During the preparation stage, the team coordinated with the school, developed training materials, and set up AI-based learning tools. In the implementation stage, students were trained to use various AI applications and platforms, such as interactive chatbots, automated grammar correction tools, and AI-driven TOEFL simulations. Through intensive mentoring, participants were encouraged to practice their reading, listening, speaking, and writing skills with the assistance of AI technologies. The evaluation results indicated that students gained significant knowledge of TOEFL learning strategies as well as the ability to effectively utilize AI to enhance their English proficiency. Furthermore, the program fostered greater motivation and self-confidence among students in preparing for the actual TOEFL test. Therefore, this community service initiative is expected to make a meaningful contribution to improving the quality of English language education at the high school level.